2017
DOI: 10.4300/jgme-d-15-00799.1
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of a Tool to Assess Quality Improvement Knowledge and Skills in Pediatrics Residents

Abstract: Background Residency programs are expected to educate residents in quality improvement (QI). Effective assessments are needed to ensure residents gain QI knowledge and skills. Limitations of current tools include poor interrater reliability and requirement for scorer training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The importance of QI competence to healthcare delivery and the development of appropriate training programs is concomitant with the recognition that there is a need to assess medical learners in a way that ensures they have acquired the necessary knowledge, skills, and attitudes that will facilitate their involvement in QI initiatives upon completion of their training. In this regard, there are a number of tools that have been shown to exhibit reliability and validity evidence, such as the Quality Improvement Knowledge Application Tool (QIKAT-R) [ 8 ], the Assessment of Quality Improvement Knowledge and Skills (AQIKS) instrument [ 9 ], and the Mayo Evaluation of Reflection on Improvement Tool (MERIT) [ 10 ]. In each case, the research has shown these tools to have some utility; however, they are resource intensive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of QI competence to healthcare delivery and the development of appropriate training programs is concomitant with the recognition that there is a need to assess medical learners in a way that ensures they have acquired the necessary knowledge, skills, and attitudes that will facilitate their involvement in QI initiatives upon completion of their training. In this regard, there are a number of tools that have been shown to exhibit reliability and validity evidence, such as the Quality Improvement Knowledge Application Tool (QIKAT-R) [ 8 ], the Assessment of Quality Improvement Knowledge and Skills (AQIKS) instrument [ 9 ], and the Mayo Evaluation of Reflection on Improvement Tool (MERIT) [ 10 ]. In each case, the research has shown these tools to have some utility; however, they are resource intensive.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the contextually bound nature of these tools is particularly challenging when one considers the assessment of QI knowledge, skills, and attitudes that are developed via training programs that are situated outside of the clinical context (e.g., PRIME). In situations such as these, these tools lack utility because their development is predicated on application testing and validity evidence derived from clinical settings [ 6 , 7 , 9 ]. Given the importance of QI training in health professions education, new assessment tools are needed that can reliably measure knowledge, skills, and attitudes following educational interventions.…”
Section: Introductionmentioning
confidence: 99%
“…The curriculum could be taught using various case-based learning strategies that simulate real-life experiences in a time-compressed manner that implement our proposed learning objectives (Appendix SA5). [32][33][34] Review of these cases would be done through online videos created by QI experts at outside institutions to overcome the lack of local PHO QI expertise, although local non-PHO faculty with QI expertise could assist.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, there have been some notable examples on the development and reporting of specialty-specific structured QI curricula outside surgery. These include: psychiatry, [43][44][45][46] family medicine, [47][48][49] internal medicine, [50][51][52][53][54] medicine, 55,56 preventive medicine, 57,58 child neurology, 59 pediatric medicine, 60 interdisciplinary pediatric medicine, [61][62][63][64][65] neonatal intensive care, 66 respiratory subspecialties, 67 anesthesiology, 68 palliative care, 69 physical medicine and rehabilitation, 70 geriatric residency, 71 and obstetrics-gynecology. 72 QI courses are reported in undergraduate 73,74 and graduate medical education.…”
Section: Discussionmentioning
confidence: 99%